Positive Effect of Elevated p-Cresol Level in the Brain through the Experiment on Rats: Insights from Active Avoidance Testing - Tevzadze, Gigi; Kikvidze, Zaal (Contemporary Research and Perspectives in Biological Science Vol. 4, 2024)
The present study highlights the positive effect of elevated p-cresol levels in the brain through the experiment on rats. It is established that p-cresol, a compound produced by bacterial colonies within the gastrointestinal tract of mammals, plays a contributory role in the manifestation of various mental disorders, including Autism, Epilepsy, Parkinson's, Alzheimer's, depression, etc. However, contrary to existing consensus, it was recently found that lowering the level of p-cresol in the brain of rats leads to a decrease in cognitive activity and, significantly affects the social projection of cognitive activity. The aim of the study is to investigate the impact of augmenting p-cresol levels in the brain on learning. The Active Avoidance Test was employed to assess learning capabilities. The results, with a high confidence level, for the first time, indicated that rats with an increased concentration of p-cresol in the brain exhibited superior task performance and accelerated learning compared to the control group. This research initiates a new understanding of the relationship between gut microbiota and the brain, highlighting the beneficial role of substances produced by gut microbiota in brain function.